Illness narratives of substance users from urban India: The untold stories of their ‘afflictions’ (Medicine Anthropology Theory, 2017)
Reading Veena Das’s book 'Affliction: Health, Disease, Poverty' was a journey of revelations for me as a health professional. The various dialects of illness that are spoken in the rapidly urbanizing Indian community become coherent, lending a voice to the distinctive sociocultural distress of the men and women who form a part of it. A discussion of the social aspects of illness brings certain questions to mind: Does the medical community fully understand those it tries to help? Is the therapeutic dialogue about the social dimensions of medical problems or vice versa? How do we bridge the mental health gender gap in our societies? To try and find some answers, I present the illness stories of two women who sought treatment at drug abuse treatment clinics in the urban slums of New Delhi. This think piece describes substance use disorder in the context of the cultural processes that have shaped these women, their families, and society.